More Incentives — Less Sanctions: a Proposal for a Reform of the Welfare System - Friedrich Breyer (Wirtschaftsdienst)
Abstract The German federal government is planning a radical reform of the basic income scheme for the long-term unemployed. Besides strengthening qualification measures and removing the priority on job placement they want to improve the additional income rules for transfer recipients. To achieve this goal, they must solve the puzzle of how to reduce the almost prohibitively high transfer withdrawal rates in case of own earnings without rendering the whole system too expensive. The solution presented is a variation of the “workfare” model by Besley and Coate (1992) and consists of two elements: lowering the basic allowance for those who do not want to work and providing a job guarantee for those willing to work so that all persons capable of work can contribute to covering their consumption needs.